Stroke patients’ adherence to nurses’ advice and their quality of life after admittance to Hospital Tengku Ampuan Afzan - Ibrahim, Wisam Nabeel; Md Nawi, Sufi; Abdullah Al-Mahmood, Sinan Mohammed; Othman, Noratikah (IIUM Press, 2018)
Objective: The objective of this study is to identify stroke patients’ adherence toward nurses’ advice and quality of life. Methodology: This was a cross-sectional study conducted at a medical ward in Hospital Tengku Ampuan Afzan, Kuantan, Pahang; it used the Quality of Life Index Stroke Version-III and Medical Outcome Study Measure of Patient Adherence. The data were collected using the purposive sampling method and were analysed using SPSS version 19. Results: A total of 54 respondents, ranging in age from 50 to 80 years old, (46.3% male and 53.7% female) with 94.4% being Malays. Returned surveys indicated that 50% of the respondents have no formal education. A total of 64.8% patients adhered to the nurses’ advice and the remaining 35.2% were non-adherents.There is a positive correlation between adherence and the quality of life. Male patients demonstrated a better adherence level compared to women (p=0.019). However, there was no association between age, race and education level with adherence. Conclusion: Healthcare professionals, such as nurses, have substantial roles in ensuring stroke patients adhere to rehabilitation guidelines with a view to maximising the quality of life.